The Amidah in Rabbinic Liturgy: Creation or Adaptation? - del Barco del Barco, Javier (’Ilu. Revista de Ciencias de las Religiones, 2019)
This article discusses one of the most controversial topics on the creation of Rabbinic Jewish Liturgy—the origin of the Amidah, the main prayer in the Jewish religious public service, after the destruction of the Second Temple in 70 E. C. To this end, the formal and literary structure of the Amidah is analyzed followed by a critical discussion on its origin that contributes to the scholarly debate on the topic. An annotated Spanish translation of this first-century prayer is rendered as an Appendix.